2019
DOI: 10.3390/biom9100525
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Attenuates Fibrotic Processes by Downregulating TGF-β1/Smad3 in Early Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) involves damage associated to hyperglycemia and oxidative stress. Renal fibrosis is a major pathologic feature of DN. The aim of this study was to evaluate anti-fibrogenic and renoprotective effects of all-trans retinoic acid (ATRA) in isolated glomeruli and proximal tubules of diabetic rats. Diabetes was induced by single injection of streptozotocin (STZ, 60 mg/Kg). ATRA (1 mg/Kg) was administered daily by gavage, from days 3–21 after STZ injection. ATRA attenuated kidney injury thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…All of these molecular modifications were reversed by ASC-EV administration. Renal damage and TGF-β upregulation are also associated in diseases, such as diabetes 27 …”
Section: Discussionmentioning
confidence: 99%
“…All of these molecular modifications were reversed by ASC-EV administration. Renal damage and TGF-β upregulation are also associated in diseases, such as diabetes 27 …”
Section: Discussionmentioning
confidence: 99%
“…ATRA is reported to be an anti-fibrosis agent in many diseases. In past decades, studies indicated that the ATRA can alleviate the fibrosis in pulmonary fibrosis [ 25 ], diabetic nephropathy [ 1 , 26 ], etc. In our studies, we found that ATRA can reduce the RIF index and down-regulate the protein expressions of Col-IV, FN and TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, TGF-β1 facilitates the accumulation of neutrophils ( 119 , 120 ), therefore inhibiting TGF-β1 effectively alleviates neutrophil infiltration and inflammation ( 121 ). Furthermore, TGF-β1 signaling can be blocked by preventing Smad3 activation, which has been proposed as a potential therapeutic strategy for fibrotic diseases driven by neutrophil-mediated inflammation ( 122 , 123 ).…”
Section: Tgf-β1 In Adaptive Immunity Of Ckdmentioning
confidence: 99%